Performance and structures of the German science system 2021 - Dimity Stephen; Stephan Stahlschmidt (Expertenkommission Forschung und Innovation (EFI), 2021)
This study updates the annual comparative analysis of the performance and structures of the German science system. We use several bibliometric indicators of productivity, impact, and international collaboration to assess Germany's performance for the period 1995-2019 compared against 22 countries and the EU13, EU14, EU27, and OECD country groups, and an intra-Germany assessment of six sectors of the science system. Overall, all countries increased their scientific productivity over time, with particularly strong growth in China and India. China now produces nearly 25 percent of global publications and the USA, Germany, and other leading countries have accordingly lost shares. Germany continued to publish in highly visible journals and attract above-average citations. Notably, China increased both its visibility and impact to above-average levels for the first time in 2017. International collaboration continued to increase, and Germany now collaborates on 60 percent of publications, up from 50 percent a decade ago, a level in line with other large European countries, and remains a sought-after collaboration partner alongside the USA.
Keywords: 330; Wissenschaft; Bibliometrie; Forschungsevaluation; Internationaler Wettbewerb; Deutschland